Exclusive χ(2P) production in Υ{hooked}(3S) decay - CRAWFORD, G. (Institutional Knowledge at Singapore Management University, 1992)
Using the CsI calorimeter of the CLEO-II detector, we have studied exclusive radiative decays of the ϒ(3S) to the χ(2P) states where the final state consists of two photons and two leptons (e+e− or μ+μ−, from either the ϒ(1S) or ϒ(2S)). We observe and measure branching ratios for the J=2 and J=1χb(23PJ) states, and set upper limits for the J=0 state.